(untitled) (JÓVENES EN LA CIENCIA, 2022)
Comanjilla is a town belonging to the municipality of Silao, Gto., which has within its limitations the presence of sulfur-thermal waters and geysers that have their origin by a geological fault that crosses the vicinity of the Sierra de Guanajuato. When the water runs down the walls of this fault, it reaches depths that make possible an increase in temperature, reaching levels suitable for the growth of different extremophilic microorganisms. In this research, microscopic analysis of microbial mat and water samples from the thermal zones of Comanjilla, Gto. was carried out to identify the microorganisms present, particularly diatoms.